Assessment for learning: practices among Agricultural ILS teachers in Malaysia - Pyng, How Shwu; Mat Rashid, Abdullah (EuroJournals, 2018)
This study employed a cross-sectional survey research design to determine the assessment for learning practices among teachers who teach Agricultural Integrated Living Skills (ILS) subject in Malaysia. The instrument used is a set of questionnaire which engaging Agricultural ILS teachers in secondary schools throughout Malaysia as samples. The purposes of this study specifically focused on the level of assessment for learning practices and explore the selected demographic factors toward practices of assessment for learning among Agricultural ILS teachers in Malaysia. The finding shows that the level of assessment for learning practices among Agricultural ILS teachers were mostly at the moderate level. Furthermore, findings also shows assessment for learning practices significant related to the highest educational qualification among Agricultural ILS teachers. Several recommendations are made based on the findings especially for the alignment of assessment for learning practices among teachers in schools.